Transcriptomic and proteomic responses of the oceanic diatom Pseudo‐nitzschia granii to iron limitation - Natalie R Cohen; Weida Gong; Dawn M. Moran; Matthew R. McIlvin; Mak A. Saito; Adrian Marchetti (Environmental Microbiology, 2018)
Summary Diatoms are a highly successful group of photosynthetic protists that often thrive under adverse environmental conditions. Members of the genus Pseudo‐nitzschia are ecologically important diatoms which are able to subsist during periods of chronic iron limitation and form dense blooms following iron fertilization events. The cellular strategies within diatoms that orchestrate these physiological responses to variable iron concentrations remain largely uncharacterized. Using a combined transcriptomic and proteomic approach, we explore the exceptional ability of a diatom isolated from the iron‐limited Northeast Pacific Ocean to reorganize its intracellular processes as a function of iron. We compared the molecular responses of Pseudo‐nitzschia granii observed under iron‐replete and iron‐limited growth conditions to those of other model diatoms. Iron‐coordinated molecular responses demonstrated some agreement between gene expression and protein abundance, including iron‐starvation‐induced‐proteins, a putative iron transport system and components of photosynthesis and the Calvin cycle. Pseudo‐nitzschia granii distinctly differentially expresses genes encoding proteins involved in iron‐independent photosynthetic electron transport, urea acquisition and vitamin synthesis. We show that P. granii is unique among studied diatoms in its physiology stemming from distinct cellular responses, which may underlie its ability to subsist in low iron regions and rapidly bloom to outcompete other diatom taxa following iron enrichment.